PENGARUH KINERJA PERUSAHAAN TERHADAP RETURN SAHAM (Media Riset Akuntansi, 2022)
The phenomenon of fluctuations in stock Returns in the food and beverage subsector encourages researchers to conduct research about the effect of company performance based on the Piotroski F-Score on stock Returns. Piotroski F-Score is one of the fundamental analysis methods that investors can use before making investment decisions. Several variabels of the company's financial condition based on the Piotroski F-Score were also investigated. These variabels are profitability, solvency, liquidity and operational efficiency. The population of this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020 with a total population of 140. The sample selection technique used is purposive sampling. The sample size obtained based on this method is 83. The analytical method used is multiple linear regression. The results showed that operational efficiency and Piotroski F-Score had a positive effect on stock Returns, while profitability, solvency and liquidity had no effect on stock Returns.